PEMBERIAN LIMBAH CAIR BIOGAS PADA TANAMAN SAWI (Brassica juncea L.) - Henry ' Simatupang; Hapsoh ' '; Husna ' Yetti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
ABSTRACT This research aims to determine the effect of bioslurry fertilizer get the best on growth and production of mustard plant. This research was conducted at the experimental farm of the Faculty of Agriculture, University of Riau, Pekanbaru from January 2016 to February 2016. This research arranged experimentally using Completely Randomized Design (CRD),of 5 treatments with 4 replications then obtained 20 experimental units, the experimental units consisted of 25 plants. The treatments is the bioslurry fertilizer ( B): B0 = 0 bioslurry, B1= 9 ml bioslurry/plants, B2 = 19 ml bioslurry/plants, B3 = 29 ml bioslurry/plants, B4= 39 ml bioslurry/plants. Parameters measured were plant height (cm), number of leaves (pieces), leaves widht(cm2), plant fresh weight (g), plant weight unfit for consumption (g). Provision of bioslurry significant effect on and bioslurry 29 ml give the best results in parameter that is 18.45 cm plant height, number of leaves 14.62 pieces, leaves widht 165.62 cm2, 82.33 g of plant fresh weight, plant weight 35.03 g unfit for consumption. Keywords: Bioslurry, Mustard Plants.